The use of tranexamic acid for on‐demand and prophylactic treatment of hereditary angioedema—A systematic review. Issue 4 (20th September 2018) - Horiuchi, Takahiko; Hide, Michihiro; Yamashita, Kouhei; Ohsawa, Isao
Abstract: Hereditary angioedema (HAE), caused by inherited deficiency of C1 esterase inhibitor (C1‐INH), is characterized by recurring subcutaneous and/or submucosal edema. Although its efficacy remains controversial, tranexamic acid (TXA) is used to treat HAE in some countries. We analyzed TXA as an on‐demand and prophylactic treatment in patients with HAE. Published data were systematically sourced from PubMed and Embase. All retained articles underwent grading/bias assessment using the "SIGN" grading system, and the quality of retained studies was determined following assessment of design and methodology. Of 353 studies identified, 31 were included. On‐demand treatment and prophylactic treatment were assessed in five (N = 103) and 28 studies (N = 231), respectively. The majority of studies (80%) demonstrated that on‐demand TXA was ineffective for skin, abdominal, or laryngeal swellings. In a single randomized controlled trial, the median time to relief of symptoms was 2 and 12 hours for icatibant and TXA, respectively ( P < 0.001). For prophylaxis, while 50% of case series, case reports, and observational studies reported beneficial effects of TXA, newer therapies, for example, icatibant and pdC1‐INH, were more effective. One study found that breakthrough attacks during TXA prophylaxis lasted significantly longer compared with C1‐INH (median time to resolution; 7 vs 3 hours, P = 0.016). Many studies failed to report safety data (16/31, 52%); however, pruritus, vomiting, and diarrhea were noted in some patients. There is no evidence for on‐demand use of TXA in HAE and limited evidence for prophylaxis. While TXA may be more beneficial than no treatment, newer, more effective therapies should be used when available. Abstract : Hereditary angioedema (HAE) is caused by inherited deficiency of C1 esterase inhibitor (C1‐INH), and tranexamic acid is used to treat HAE in some countries. We systematically reviewed relevant literature and showed that there is no evidence for the on‐demand use of TXA in HAE and limited evidence for prophylaxis. While TXA may be more beneficial than no treatment, newer, more effective therapies should be used when available.